Biomechanical analysis of sagittal correction parameters for surgical instrumentation with pedicle subtraction osteotomy in adult spinal deformity. (January 2020) - Benoit, David; Wang, Xiaoyu; Crandall, Dennis G.; Aubin, Carl-Éric
Abstract: Background: High complication rate has been documented in spinal instrumentation with pedicle subtraction osteotomy. The objective was to analyze the biomechanics of spinal instrumentation with pedicle subtraction osteotomy as functions of three instrumentation parameters. Methods: Patient-specific biomechanical computer models of 3 adult patients who were instrumented with pedicle subtraction osteotomy were used to simulate the actual instrumentations and alternative instrumentations derived by varying instrumentation parameters: pedicle subtraction osteotomy wedge angle and rod contouring angle, location of the osteotomy, and number of rods (2 vs. 4). Findings: A change of the sagittal correction by +7.5° (−7.5°) resulted in a change in the screw axial forces and rods bending loads around the osteotomy by +38% (−19%) and +28% (−11%), respectively. The bending moments in the rods were 31% lower at the osteotomy site when it was located at one level above, and 20% higher when it was located at a level below. Additional rods allowed the rod bending and screw axial loads to be reduced by 24% and 22%, respectively. Interpretation: The amount of sagittal correction was positively correlated with loads sustained by the screws and rods. Rods were subjected to higher bending loads at the pedicle subtraction osteotomy site when it was done at a lower level. A 4-rod construct is an effective way to reduce the risk of rod breakage by reducing the loads sustained by the rods. Highlights: Pedicle subtraction wedge angle was positively correlated with construct loads. More caudally located pedicle subtraction had higher construct loads. 4-rod constructs (vs. 2 rods) reduced the construct loads.